Structural analysis of the JBW (Na-J, barrer and white) zeotype obtained from kaolinite-rich clay - Macías-López, Mario Alberto; Ríos-Reyes, Carlos Alberto; Castellanos-Alarcón, Oscar Mauricio (Universidad Pedagógica y Tecnológica de Colombia, 2018)
The JBW zeolite was prepared from hydrogels under hydrothermal conditions by alkaline reaction, using NaOH as activating agent. The synthetic zeotype was studied by analytical techniques such as X-ray powder diffraction, scanning electron microscopy, Fourier transformed infrared spectroscopy and solid-state 29Si and 27Al Magic angle spinning nuclear magnetic resonance. Crystallographic data revealed that the JBW structure can be described by the orthorhombic space group Pna21, with unit cell parameters a=16.409(2) Å, b=14.966(2) Å and c=5.2154(5) Å.